Antimicrobial and antifouling hyaluronic acid-cobalt nanogel coatings built sonochemically on contact lenses - Guillem Ferreres; Sílvia Pérez-Rafael; Ester Guaus; Òscar Palacios; Ivan Ivanov; Juan Torrent-Burgués; Tzanko Tzanov (Ultrasonics Sonochemistry)
The wearing of contact lenses (CLs) may cause bacterial infections, leading in turn to more serious complications and ultimately vision impairment. In this scenario, the first step is the adhesion of tear proteins, which provide anchoring points for bacterial colonization. A possible solution is the functionalization with an antimicrobial coating, though the latter may also lead to sight obstruction and user discomfort. In this study, adipic acid dihydrazide-modified hyaluronic acid-cobalt (II) (HA-ADH-Co) nanogels (NGs) were synthesized and deposited onto commercial CLs in a single-step sonochemical process. The coating hindered up to 60 % the protein adsorption and endowed the CLs with strong antibacterial activity against major ocular pathogens like Staphylococcus aureus and Pseudomonas aeruginosa, reducing their concentration by around 3 logs. Cytotoxicity assessment with human corneal cells demonstrated viabilities above 95 %. The nanocomposite coating did not affect the optical power and the light transmission of the CLs and provided enhanced wettability, important for the wearer comfort.